Stabilisasi Sterik Polimer Non-Ionik Tween 80 pada Nanopartikel Senyawa Bioaktif Buah Kapulaga - Horasdia Saragih (Jurnal Fisika Unand, 2026)
The bioactive compounds in cardamom fruit are highly beneficial to health, as they possess anticancer, antioxidant, antibacterial, anti-inflammatory, and antibiotic properties. Therefore, they have great potential to be developed as oral medicines in the future. However, they are highly hydrophobic and consequently insoluble in water. This poses an obstacle to their development. To overcome this problem, bioactive compounds from cardamom fruit have been synthesized into nanometer-sized particles (13.13-19.75 nm) and encapsulated with the nonionic polymer surfactant Tween 80. The results show that Tween 80 surfactant not only acts as an encapsulant for nanoparticles so that they can be dispersed in an aqueous medium, but also acts as a steric stabilizer so that the nanoparticles can remain stable for a long time. Four concentrations of bioactive compounds from cardamom fruit were used, namely: 6, 8, 10, and 12 mg to observe their effect on size stability. All nanoparticles produced from the four concentrations had excellent size stability.